(untitled) (Research, Society and Development, 2021)
The sludge generated in wastewater treatment plant (WWTP) is a challenge for several cities about its destination. The ceramic brick industry has the potential to reuse this waste and can therefore be a sustainable alternative. Therefore, this work aims to identify in the literature if it is possible to apply the ETE sludge directly in the manufacturing process of the clay brick in partial substitution to the clay. The methodology used was a systematic literature review and the P.I.C.O. criteria as a starting strategy. Four exclusion criteria were used in the choice of articles and 5 scientific articles were arrived at that addressed the subject. Data related to chemical composition parameters, mixing ratio, sintering temperature, weight loss on ignition, apparent density, water absorption, linear shrinkage, mechanical resistance and metal leaching were verified, and these were compared, in each study, to the local normative limits of ceramic brick manufacture. In this work, the Brazilian standard ABNT NBR 15270-1 was also used as a comparison to the verified data. The results were promising, since in each work at least one proportion of the mixture (trace) indicating a brick within the normative limits was presented. Therefore, it is concluded that it is technically feasible to develop bricks with clay and WWTP sludge in their primary manufacture.